2001
DOI: 10.1046/j.1439-0272.2001.00428.x
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise regression analysis to study male and female factors impacting on pregnancy rate in an intrauterine insemination programme

Abstract: The aim of this study was to evaluate the impact of male and female factors on the pregnancy rate in an intrauterine insemination (IUI) programme. Data on 522 cycles were retrospectively studied. All patients 39 years or younger were included in the study where data were available on male and female diagnosis, as well as on ovulation induction methodology. Regression analysis was possible on 495 cycles to study different factors affecting the pregnancy rate per treatment cycle. Logistic regression identified v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…There are several studies that have concluded that IUI is not an effective treatment in male factor infertility [12,13]. We used the standard definition of male factor infertility using the WHO criteria for normal semen parameters in this study.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies that have concluded that IUI is not an effective treatment in male factor infertility [12,13]. We used the standard definition of male factor infertility using the WHO criteria for normal semen parameters in this study.…”
Section: Discussionmentioning
confidence: 99%
“…2001). When normal sperm morphology exceeds 14%, the chance of pregnancy after IUI is 1.8 times higher than when it is lower than 14% (Montanaro Gauci et al. 2001).…”
Section: Semen Quality In Animals and Humansmentioning
confidence: 95%
“…To achieve acceptable pregnancy rates after IUI, at least 5% of the spermatozoa have to be morphologically normal (Ombelet et al. 1997; Montanaro Gauci et al. 2001; Van Waart et al.…”
Section: Semen Quality In Animals and Humansmentioning
confidence: 99%
“…The link between sperm motility and IUI success was addressed in several studies. Briefly, in these studies, total motile sperm of 30–50% before sperm preparation was found to be associated with positive IUI outcomes [54, 56, 57]. …”
Section: Semen Parameters and The Use Of Iuimentioning
confidence: 99%